Effects of a Chelated Copper as Growth Promoter on Performance and Carcass Traits in Pigs - J. Zhao; G. Allee; G. Gerlemann; L. Ma; M. I. Gracia; D. Parker; M. Vazquez-Anon; R. J. Harrell (Asian-Australasian Journal of Animal Sciences, 2014)
Three studies were conducted to investigate whether a chelated Cu can replace CuSO4 as a growth promoter in pigs. In Exp. 1, a total of 240 piglets (Large White×Landrace, 7.36±0.10 kg) were randomly allocated to 1 of 3 treatments with 8 replicates and 10 piglets per pen. Treatments included a NRC control (CuSO4, 6 mg/kg), two Cu supplementations from either CuSO4 or Cu(HMTBa)2 at 170 mg/kg. Pigs fed Cu(HMTBa)2 were 6.0% heavier than pigs fed either the NRC control or 170 mg/kg CuSO4 (p = 0.03) at the end of the experiment. During the 42 days of experimental period, pigs fed Cu(HMTBa)2 gained 9.0% more (p = 0.01), tended to eat more feed (p = 0.09), and had better feed efficiency (p = 0.06) than those fed CuSO4. Compared with the 6 mg/kg CuSO4 NRC control, liver Cu was increased 2.7 times with 170 mg/kg CuSO4 supplementation, and was further increased with Cu(HMTBa)2 (4.5 times, p<0.05). In Exp. 2, a total of 616 crossbred piglets (PIC, 5.01±0.25 kg) were randomly allocated to 1 of 4 treatments with 7 replicates and 22 piglets per pen. Treatments included a NRC control (from CuSO4), and three pharmaceutical levels of Cu (150 mg/kg) supplemented either from CuSO4, tri-basic copper chloride (Cu2[OH]3Cl), or Cu(HMTBa)2. Pigs fed CuSO4 or Cu(HMTBa)2 had better feed efficiency (p = 0.01) and tended to gain more (p = 0.08) compared with those fed the NRC control. Pigs fed Cu2(OH)3Cl were intermediate. Pigs fed Cu(HMTBa)2 had the highest liver Cu, which was significantly higher than those fed (Cu2[OH]3Cl) or the negative control (p = 0.01). In Exp. 3, a total of 1,048 pigs (PIC, 32.36±0.29 kg) were allotted to 6 treatments with 8 replicates per treatment and 20 to 22 pigs per pen. The treatments included a NRC control with 4 mg/kg Cu from CuSO4, a positive control with 160 mg/kg Cu from CuSO4, and incremental levels of Cu(HMTBa)2 at 20, 40, 80, and 160 mg/kg. During the overall experimental period of 100 days, no benefit from 160 mg/kg CuSO4 was observed. Pigs fed Cu(HMTBa)2 had increased ADG (linear and quadratic, p≤0.05) and feed efficiency (linear and quadratic, p≤0.05) up to 80 mg/kg and no further improvement was observed at 160 mg/kg for the whole experimental period. Pigs fed 80 mg/kg Cu(HMTBa)2 weighed 1.8 kg more (p = 0.07) and were 2.3 kg heavier in carcass (p<0.01) compared with pigs fed 160 mg/kg CuSO4. In addition, loin depth was increased with increased Cu(HMTBa)2 supplementation with pigs fed 80 mg/kg Cu(HMTBa)2 had the greatest loin depth (p<0.05). In summary, Cu(HMTBa)2 can be used to replace high CuSO4 as a growth promoter in nursery and grower-finisher pigs.